THE ESSENCE OF INTEGRATION IN SCHOOL MATHEMATICS EDUCATION AND ITS PSYCHOLOGICAL ROLE IN TEACHING - Kuchkarova Fazilat Khankeldievna; Nazarov Xoliqul Eshmurodovich; Isroilova Dilshoda; Khamitova Mokhigul (Bright Mind Publishing, 2025)
This article discusses the main functions of integration in mathematics education, the essence of integrative processes, the distinction between the concepts of "Integration of Sciences" and "Integration of Scientific Knowledge," and how the meaning of the word "integratio" and the mathematical term derived from it do not fully capture their content. The article also presents the opinions of several scholars on the concept of integration. Additionally, it addresses the application of geometric methods in algebra and their role, the importance of geometry in mechanics and physics, the role of integration in the development of spatial imagination, and in the formation of mathematical intuition.
Keywords: Integration of Sciences, integrative process, function, integratio, culture, geometric, algebra, integration of scientific knowledge.